Biology And Population Dynamics Of Mango Flower Thrips (Thysanoptera) And Effectiveness Of Neem (Azadirachta Indica) Oil For Their Control - Aliakbarpour, Hamaseh (2011)
Population dynamics of thrips was investigated in treated and untreated mango orchards, located at Balik Pulau, Penang between 2008 and 2010. Thrips abundance was estimated by collecting them from mango panicles and various weed species growing in the orchard. Four thrips species from the family Thripidae; Thrips hawaiiensis, Scirtothrips dorsalis, Frankliniella schultzei and Megalurothrips usitatus were recorded from the treated orchard. Other than these species, Thrips palmi (Thripidae) and Haplothrips sp. (Phlaeothripidae) were encountered in the untreated orchard. Comparing several thrips collection techniques with the absolute population count, CO2 collection method was the most efficient procedure, extracting 80.7% adults, followed by the washing procedure (62.3%) and the shaking method (36.4%).